Ausländische Direktinvestitionen in Deutschland~– die große Angst vor China - Holger Görg (Zeitschrift für Wirtschaftspolitik, 2019)
The current discussion in German policy circles suggests a strong scepticism towards foreign takeovers of German firms. This essay takes issue with this. It is firstly argued that Germany in actual fact receives relatively little inward investment. The essay then discusses the potential benefits from inward FDI which could also benefit the German economy. It then briefly reflects on the German policy initiatives which seem to be based on a fear of investment from China - though it is not clear at all what this fear is based on.
Keywords: 330